Novel nanocomposites obtained by dispersion of LDH modified with N‐tetrabromophthaloyl‐glutamic in poly(amide‐imide) having N‐trimellitylimido‐l‐leucine and 4, 4′‐diaminodiphenylether units. Issue 5 (6th November 2014) - Mallakpour, Shadpour; Dinari, Mohammad; Talebi, Meysam
Abstract : Layered double hydroxides (LDHs) have attracted much attention as nanofillers in polymer nanocomposites (NCs) due to their particular surface structural, positively charged layer and so on. In this study, a chiral diacid was synthesized by the reaction of tetrabromophthalic anhydride and glutamic acid. LDH was modified by co‐precipitation of aluminum nitrate, magnesium nitrate, and glutamic acid containing diacid. Chiral poly(amide‐imide) (PAI) was synthesized by direct polycondensation reaction of N ‐trimellitylimido‐l ‐leucine and 4, 4′‐diaminodiphenylether. Different NCs of the obtained modified LDHs and the chiral PAI were prepared in a short time using ultrasonic technique. The morphology and the structure of the obtained samples were characterized by Fourier transform infrared, thermogravimetric analysis (TGA), field emission scanning electron microscopy, transmission electron microscopy, and X‐ray diffraction analysis. TGA of the NCs showed a special order in thermal stability in compression with the neat PAI owing to the uniform distribution of the nanofillers. POLYM. COMPOS., 37:1323–1329, 2016. © 2014 Society of Plastics Engineers